Chaos in a Pro-Life Event: An Analysis of Negative Impoliteness - afriana, afriana; Ambalegin, Ambalegin; Aslan, Imran; Natanael, Yosua Timotius (Asosiasi Ide Bahasa Kepri, 2024)
A Pro-life event held by Student for Life turned chaotic. This phenomenon can be attributed to the occurrence of negative impoliteness strategies, which attack one’s negative face-wants. This research is aimed to analyze the strategies and the functions of negative impoliteness in the event. This research is descriptive-qualitative, using observational and non-participatory techniques for the data collection. The collected data were analyzed according to the theory of Culpeper (1996, 2011) for the strategies of negative impoliteness and their functions. The results showed that there were negative impoliteness strategies done by the pro-choice audience to frighten, condescend, ridicule, scorn, invade, explicitly associate with negative aspects, and hinder the pro-life speakers and members, which were functioning as coercive and affective impoliteness, consequently turned the event chaotic. They knew and were able to act polite, but decided not to. Arguments aside, both parties should have engaged in a professional and mature attitude.